Simulação de reservatórios não convencionais para armazenamento de gás natural veicular - Vilhena, John Edward Neira (2004)
The investigation of viability to use containers for Natural Gas Vehicle (NGV) storage, with different geometries of commercial standards, come from necessity to join the ambient, financial and technological benefits offered by the gas combustion, to the convenience of not modify the original proposal of the automobile. The use of these current cylindrical models for storage in the converted vehicles is justified by the excellent behavior that this geometry presents about the imposed tensions for the high pressure that the related reservoirs are submitted. However, recent research directed toward application of adsorbent materials in the natural gas reservoirs had proven a substantial redusction of pressure and, consequently, a relief of the tensions in the reservoirs. However, this study considers alternative geometries for NGV reservoirs, searching the minimization of dimensions and weight, remaining capacity to resist the tensions imposed by the new pressure situation. The proposed reservoirs parameters are calculated through a mathematical study of the internal pressure according to Brazilian standards (NBR) for pressure vessels. Finally simulations of the new geometries behavior are carried through using a commercially avaible Finite Element Method (FEM) software package ALGOR® to verify of the reservoirs efficincy under the gas pressure load